Curcumin-Based β-Diketo Ligands for Ga3+: Thermodynamic Investigation of Potential Metal-Based Drugs - Matteo Mari; Debora Carrozza; Gianluca Malavasi; Ettore Venturi; Giulia Avino; Pier Cesare Capponi; Michele Iori; Sara Rubagotti; Silvia Belluti; Mattia Asti; Erika Ferrari (Pharmaceuticals, 2022)
Curcumin is known for its therapeutic properties; among these, antioxidant, anti-inflammatory and anti-cancer ones stand out. Besides, curcumin metal complexes have shown widespread application in medicine and can be exploited as lead structures for developing metal-based drugs. Unfortunately, curcumin is poorly bioavailable, mainly due to its instability in physiological conditions; this weakness is tightly connected to the presence of the β-diketo moiety undergoing tautomeric equilibrium. Stability and metal-chelating ability can be tuned by modulating the electronic effects and steric hindrance close to the β-diketo moiety; in addition, formation of a metal complex shifts the tautomeric equilibrium towards the β-keto–enol form and increases stability in biological media. Among the metals used in clinical therapy, gallium nitrate has shown to have significant antitumor activity against non-Hodgkin lymphoma and bladder cancer, thus indicating that gallium-based drugs have potential for further development as antineoplastic agents with improved therapeutic activity. Curcuminoids have demonstrated high affinity for gallium(III), allowing the formation of stable positively charged M:L 1:2 β-diketonate complexes that benefit from the therapeutic activity of both the metal and the ligand. Seven new curcumin derivatives were synthesized and completely characterized. The new derivatives retain the solvent-dependent keto–enol tautomerism, with the prevalence of the diketo form in aqueous solution. Enhanced stability in simulated physiological conditions was observed in comparison to the lead compound curcumin. The presence of Ga3+ anticipates the dissociation of the enolic proton, allowing chelate complex formation, and simultaneously it shifts the tautomeric equilibrium towards the keto–enol form. A complete 1H/13C NMR and UV–Vis study was performed to define the metal-to-ligand stoichiometry ratio and the overall stability constants. In addition, we demonstrated that some of the derivatives have increased antiproliferative activity on colon cancer cells compared to curcumin and antioxidant properties. On the whole, the synthesized curcumin-based molecules may act as new gallium(III) chelators with improved stability with respect to curcumin and could open interesting perspectives for the development of novel therapeutic agents for cancer.